2021
DOI: 10.3389/fpsyg.2021.623643
|View full text |Cite
|
Sign up to set email alerts
|

Media Multitasking: A Bibliometric Approach and Literature Review

Abstract: Media multitasking became increasingly popular over the past decade. As this behavior is intensely taxing cognitive resources, it has raised interest and concerns among academics in a variety of fields. Consequently, in recent years, research on how, when, and why people media multitask has strongly emerged, and the consequences of the behavior for a great variety of outcomes (such as working memory, task performance, or socioemotional outcomes) have been explored. While efforts are made to summarize the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 124 publications
0
6
0
1
Order By: Relevance
“…Interestingly, in our data the sign of the relationship between multitasking costs and multi-media use also changes with age from positive in young participants to negative in older participants, suggesting that the demographic composition of participant groups may have significantly influenced the pattern of results observed in previous studies. Indeed, in a recent review, Beuckels et al 24 highlight that older adults are extensive media-multitaskers and note that this group have received little to no research attention, thus the present work addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, in our data the sign of the relationship between multitasking costs and multi-media use also changes with age from positive in young participants to negative in older participants, suggesting that the demographic composition of participant groups may have significantly influenced the pattern of results observed in previous studies. Indeed, in a recent review, Beuckels et al 24 highlight that older adults are extensive media-multitaskers and note that this group have received little to no research attention, thus the present work addresses an important gap in the literature.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, it remains unknown whether such changes across the life-span are influenced—for better or worse—by multimedia technology use. Indeed, in a recent review, Beuckels et al 24 identified that there is an important research gap in the field of media multitasking, in which younger and older media multitaskers have received little to no research attention. Thus, our research addresses an important outstanding issue in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the inclusion of the 4.0 revolution agenda and the era of disruption in these various fields, multitasking media behavior is increasingly rampant (Lang et al, 2015) mentions that multitasking media is defined as the state in which a person performs two tasks simultaneously, one involving media use. According to Beuckels et al (2021) media multitasking is when a person performs two or more tasks using media simultaneously, either using media on one or more of the tasks. Therefore, the behavior of multitasking media is a person's activity in using more than one technological media simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, well-structured bibliometric studies can form a sound basis to develop an area in unique and significant ways and guide the researchers for future studies (18). There are a few bibliometric analyses on multitasking in psychology (20,21). However, there is no bibliometric analysis of dual-task studies the popularity of which is gradually increasing in physiotherapy and rehabilitation today.…”
Section: Introductionmentioning
confidence: 99%